Exploring the effect of aplidin on low molecular weight protein tyrosine phosphatase by molecular docking and molecular dynamic simulation study. (December 2019) - Sun, Ying-Zhan; Wu, Jing-Wei; Lu, Xin-Hua; Ma, Ying; Wang, Run-Ling
Graphical abstract: The changes of the interactions of the key residues (Asn15) between theLMW-PTP and LMW-PTP/aplidin systems. Highlights: The study of the mechanism of molecular basis of the ligand-aplidin inhibition of the LMW-PTP for the first time. The study was to reveal the interactions of ligand with residues in the active site of LMW-PTP by MD simulations. The Asn 15 was first found as the key residue, which plays an important role in disturbing the residue interactions. Abstract: The low molecular weight protein tyrosine phosphatase (LMW-PTP) could regulate many signaling pathways, and it had drawn attention as a potential target for cancer. As previous report has indicated that the aplidin could inhibit the LMW-PTP, and thus, the relevant cancer caused by the abnormal regulation of the LMW-PTP could be remission. However, the molecular mechanism of inhibition of the LMW-PTP by the aplidin had not been fully understood. In this study, various computational approaches, namely molecular docking, MDs and post-dynamic analyses were utilized to explore the effect of the aplidin on the LMW-PTP. The results suggested that the intramolecular interactions of the residues in the two sides of the active site (Ser43-Ala55 and Pro121-Asn134) and the P-loop region (Leu13-Ser19) in the LMW-PTP was disturbed owing to the aplidin, meanwhile, the π-π interaction between Tyr131 and Tyr132 might be broken. The Asn15 might be the key residue to break the residues interactions. In a word, this study may provide more information for understanding the effect of inhibition of the aplidin on the LMW-PTP.